Identifying the Fields and Mechanisms of Value Co-creation in Foreign Language Institutions Using Fuzzy DEMATEL Ranking Approach (Case Study: Tehran, Iran) - Seyed Mohammad Sobhani; Morteza Soltani; Mohammad Reza Fathi (Iranian Journal of Educational Research)
Objective: The emerging concept of value co-creation marketing as a new paradigm; is a shift from an organization-based perspective to a more moderate perspective upon interactions among the organization, customers, and value co-creation experience leading to frequent mutual interaction. Co-creation amongst companies and customers is one of the most prospective areas in both consumers' cyber-space and the real world, and also quite an emerging research territory which has not been the target of particular research studies in Iran yet; however, the same handful of studies are conducted to highlight the necessity for more rigorous investigations to understand this phenomenon. This research intends to explore the value co-creation fields and mechanisms of Foreign Language Institutions located in Iran. Methods: The present study utilizes Mixed-Methods Research; initially, the main themes were extracted from the studies relevant to co-creation through Thematic Analysis Method which were verified by twenty experts and specialists selected via judgmental sampling. Then, the Pairwise Comparison Matrix questionnaires were provided and distributed amid twelve career experts by theoretical and targeted sampling for the Fuzzy DEMATEL Method in pursuance of the ranking of Fields and Mechanisms. Results: The findings expressed that value co-creation has five main Fields and 27 Mechanisms (The five main fields' subsets) in Foreign Language Institutions that can substantially contribute to the management board pursuing mutual satisfaction and sense of engagement leading to effective performance in this market of intense and cut-throat rivalry. Conclusion: The findings can be used as a basis for strengthening mechanisms of value co-creation in foreign language institutions.